2018
DOI: 10.1016/j.exger.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue inflammation in aging

Abstract: Adipose tissue has traditionally been viewed as an organ of interest within studies of obesity and diet-associated metabolic disorders. However, as studies reveal the role white adipose tissue plays as an energy storage, a lipid metabolism site, and an adipokine secretor, it has become recognized as an organ of importance for metabolic health in both the young obese and the old obese. Within the realms of aging research, the pursuit of senolytics has taken the field's spotlight, where the clearance of senescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
86
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 81 publications
1
86
0
1
Order By: Relevance
“…(Salminen et al, ; Zhang et al, )). It is also notable that the adipose dataset, a tissue with a known role in inflammaging (Mau & Yung, ), also shows an ADICT trend. Meanwhile, apoptosis is crucial for eliminating senescent cells during healthy aging and disruptions in apoptosis could lead to accumulation of dysfunctional cells over time.…”
Section: Discussionmentioning
confidence: 97%
“…(Salminen et al, ; Zhang et al, )). It is also notable that the adipose dataset, a tissue with a known role in inflammaging (Mau & Yung, ), also shows an ADICT trend. Meanwhile, apoptosis is crucial for eliminating senescent cells during healthy aging and disruptions in apoptosis could lead to accumulation of dysfunctional cells over time.…”
Section: Discussionmentioning
confidence: 97%
“…Although there is less research specifically examining adipose tissue in the context ageing compared to obesity, a role for adipose tissue in late-onset disease development has been established. Ageing is associated with increased abdominal and ectopic adipose tissue accumulation, which is linked with the onset of frailty and cardiometabolic disease ( 167 ). Moreover, organelle stress and the accumulation of senescent cells (p16INK4a+) within adipose tissue that secrete IL-6, IL-8, and TNF-α further contribute to a pro-inflammatory, dysfunctional adipose tissue with age ( 168 , 169 ).…”
Section: Immunological Ageing and Adipose Tissuementioning
confidence: 99%
“…But the findings in this study showed a marked difference in insulin resistance between young rats and old-aged rats, both groups displaying aggravation of insulin resistance during diet-induced obesity. Thus, increase in adipose tissue due to aging and obesity was clearly verified as a key factor promoting insulin resistance [26,27]. Also to cause insulin resistance [33], and active release of IL-10 and IL-4 when obesity and pro-inflammation are relatively ameliorated [6].…”
Section: Resultsmentioning
confidence: 97%